2021
DOI: 10.1002/ps.6230
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity of Bacillus thuringiensis (Bacillales: Bacillaceae) on Diatraea saccharalis (Lepidoptera: Crambidae) eggs

Abstract: BACKGROUND Bacillus thuringiensis (Bt) is a Gram‐positive bacterium that synthesizes specific protein toxins, which can be exploited for control of various insect pests, including Diatraea saccharalis, a lepidopteran that severely damages sugarcane crops. Although studies have described the effects of Bt in the larval phases of D. saccharalis, few have examined its effect on insect eggs. Herein, we studied the entomopathogenic potential of Bacillus thuringiensis serovar Aizawai GC‐91 (Bta) during D. saccharali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 80 publications
0
14
0
1
Order By: Relevance
“…This result is superior to the inviability potential of Blissus Antilles (Hemiptera: Lygaeidae) eggs (24-h old) infected by the ESALQ818 isolate (10 4 conidia/mL), at 96.7% [40]. Other studies have evaluated the mortality of D. saccharalis eggs treated with different solutions: Daquila et al [32] observed 34.98% inviability in eggs (0 -24-h old) infected by Bacillus thuringiensis isolate Aizawai GC-91 (Bacillales: Bacillaceae) and Canazart et al [31] observed that the alternative control with garlic essential oil (0.5%) made more than 60% of the eggs unfeasible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result is superior to the inviability potential of Blissus Antilles (Hemiptera: Lygaeidae) eggs (24-h old) infected by the ESALQ818 isolate (10 4 conidia/mL), at 96.7% [40]. Other studies have evaluated the mortality of D. saccharalis eggs treated with different solutions: Daquila et al [32] observed 34.98% inviability in eggs (0 -24-h old) infected by Bacillus thuringiensis isolate Aizawai GC-91 (Bacillales: Bacillaceae) and Canazart et al [31] observed that the alternative control with garlic essential oil (0.5%) made more than 60% of the eggs unfeasible.…”
Section: Discussionmentioning
confidence: 99%
“…The chorion of D. saccharalis eggs has a thin and translucid structure [31], formed by two structures, the exochorion and endochorion [32]. These structures are synthesized by ovarian follicular cells [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four concentrations (0.62, 1.25, 2.50 and 5.00 g L −1 ) were obtained after diluting the commercial product in autoclaved distilled water at a temperature of 25°C and pH 7.0. The concentrations were based on Daquila et al (2021) for the control of D. saccharalis eggs, which is an insect pest that can be a prey for lacewings in sugarcane crops.…”
Section: Methodsmentioning
confidence: 99%
“…Since chemicals from legs may be deposited at oviposition sites, we additionally hypothesised that they may protect eggs against microbial threats. Microbial infections reduce moth egg viability (Daquila et al, 2021; Hajek et al, 1996; Sikorowski et al, 2001; Tanabe & Tamashiro, 1967). Chemicals from moth legs could disinfect surfaces to prevent microbial growth.…”
Section: Introductionmentioning
confidence: 99%